Delinquency as a Consequence of Parental Warmth and Self-Efficacy: Total Sample and Individual Male and Female Mediation Analyses - Walters, Glenn (My University, 2021)
Introduction: This study’s purpose was to investigate the mediating effect of parental control self-efficacy on the parental warmth → child delinquency relationship in the mothers and fathers of early to mid-adolescent youth in a test of performance accomplishments as a prelude to parental self-efficacy. Methods: Parental warmth and control self-efficacy estimates, representing parental support and control, respectively, were provided by the mothers and fathers of 3,934 (2,010 boys, 1,924 girls) youth from the Longitudinal Study of Australian Children (LSAC) and self-reported delinquency was obtained from the child. Results: As predicted, parental control self-efficacy mediated the relationship between parental warmth and child delinquency, whereas parental warmth did not mediate the relationship between parental self-efficacy and child delinquency. When analyses were performed separately for boys and girls, the father warmth → father self-efficacy → child delinquency pathway achieved the most consistent results in boys and the mother warmth → mother self-efficacy → child delinquency pathway achieved the only significant effect in girls. Conclusions: These results suggest that performance accomplishments, as characterized by a warm parent–child relationship, led to enhanced parental control self-efficacy, which, in turn, served to inhibit future delinquency in the child, thereby lending support to a social cognitive learning theory interpretation of the parental support–control interface.
Journal of Adolescence
Keywords: Adolescents and youth